Comparison of Two Automated Urine Analyzers (URiSCAN Super + YD Diagnostics and Sysmex UC-3500–UF-5000 Urine Chemistry Analyzer) with Routine Microscopy - Durre Aden; Poonam Khambra; Sunil Ranga; Yasir Alvi (Archives of Medicine and Health Sciences)
Background and Aim: Urinalysis is one of the most commonly performed screening tests in the clinical laboratory to diagnose and monitor various urological as well as systemic conditions. Newly developed automated urine analyzers are expected to routinely screen urine in less time compared to conventional routine microscopy and provide clinicians with prompt clinical information with a lower false-negative rate. The study aimed to evaluate the diagnostic performance of the two automated urine analyzers, URiSCAN Super + YD Diagnostics and Sysmex UC-3500–UF-5000 urine analyzer and compare them with microscopy. Materials and Methods: This was a prospective study performed on 124 randomly selected samples of patients coming to the clinical pathology laboratory at a tertiary care hospital for 3 months between March 1, 2022 and May 30, 2022. Each sample was taken for both automated analyzer testing and microscopic evaluation. The results of urine examination consisting of cells, formed elements, and microorganisms were compared between both the automated urine analyzers and microscopy, and the degree of concordance was calculated utilizing Cohen’s kappa (κ) analysis to see the concordance between all three values. The statistical analyses were performed using SPSS version 25, developed by IBM Co, and P < 0.05 was considered statistically significant. Results: The degree of concordance of red blood cell (RBC), white blood cell (WBC), and epithelial cells (ECs) was good between the two automated analyzers, URiSCAN Super + YD Diagnostics and Sysmex UC-3500–UF-5000 urine analyzer and microscopy with P < 0.05. The concordance between the Sysmex UC-3500–UF-5000 urine analyzer and manual microscopy was better than between manual microscopy and URiSCAN Super + YD Diagnostics. There was no concordance between any of these methods for either crystals, cast, bacteria, and fungi with P > 0.05. Conclusion: The results from the automated analyzers for RBCs, WBCs, and ECs were similar to the result of manual microscopy, and the analyzers can be relied on for testing and can help in reducing turnaround time of routine urine examination. However, bacteria, fungi, dysmorphic red cells, casts, and crystals need to be analyzed by microscopic examination before giving a final diagnosis.